THE ROLE OF TASK MASTERY CLIMATE AND HISTORY OF COMPETITIVE DEFEAT ON THE RESILIENCE OF TAEKWONDO ATHLETES IN MAGELANG CITY - Willyam Willyam; Sahri Sahri (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2026)
Resilience is a crucial psychological factor in competitive sports, directly relating to an athlete's ability to withstand and recover from competitive pressure. This study aims to analyze the influence of task mastery climate and the history of competitive defeat on the resilience of Taekwondo athletes in Magelang City. The study employed a quantitative approach with a correlational design. The sample consisted of 30 Taekwondo athletes in Magelang City who actively participated in training programs and competitions, selected through purposive sampling. The research instruments included the Perceived Motivational Climate in Sport Questionnaire (PMCSQ) to measure the task mastery climate and the Connor-Davidson Resilience Scale (CD-RISC) to evaluate athlete resilience. Data were analyzed using multiple linear regression. The results indicated that the task mastery climate had a positive and significant effect on athlete resilience (β = 0.47; p = 0.04). Conversely, the history of competitive defeat did not significantly influence athlete resilience (β = 0.12; p = 0.89). A simultaneous test revealed that both variables collectively did not exert a significant influence on athlete resilience (F = 2.86; p = 0.07). The coefficient of determination (R²) of 0.175 signifies that the research model explains 17.5% of the variance in athlete resilience. These findings confirm that psychosocial environmental factors, specifically the task mastery climate fostered during training, play a more consistent and pivotal role in shaping resilience compared to the mere experience of competitive defeat